MIDWIFERY CARE FOR THE NEONATE OF MRS. N IN MEUNASAH KRUENG VILLAGE, SUB-DISTRICT INGIN JAYA , THE REGENCY OF ACEH BESAR : Midwifery Care for Neonate - Isyfi Maradhani; Nizan Mauyah; Sulastri Sulastri (Department of Midwifery, Health Polytechnic of Aceh, 2026)
Infant Mortality Rate (IMR) and neonatal mortality remain major challenges in public health. The neonatal period is a critical period of adjustment from the intrauterine to the extrauterine environment, which significantly determines the infant's future survival. This case report aims to provide comprehensive midwifery care for a neonate and document it in SOAP format. This midwifery care was provided to Mrs. N, a neonate in Meunasah Krueng Village, Ingin Jaya District, Aceh Besar Regency, in 2026. Subjective data showed a normal birth, an immediate strong cry, and good breastfeeding. Objective examination results showed the baby's general condition was good, her consciousness was clear and alert, and her vital signs were stable: pulse 138 beats/minute, respiration 45 breaths/minute, and temperature 37°C. Anthropometric examination results were within normal limits. Essential midwifery care provided includes neonatal visits (KN) according to minimum service standards, counseling on clean and dry umbilical cord care, guidance on essential breastfeeding techniques for exclusive breastfeeding, implementation of Integrated Management of Young Infants (MTBM), and education on danger signs in neonates. Care outcomes indicate that parents understand the counseling provided, can demonstrate independent infant care, and are willing to adhere to the complete neonatal visit schedule. Quality and continuous midwifery care is expected to detect the risk of complications early in the first month of life. This helps reduce infant mortality.